Community Awareness and Involvement in River Conservation in Pasir Mas, Kelantan - See, Too Kay Leng; Chan, Ngai Weng; Samat, Narimah (European Publisher, 2019)
River water resources are very important for human society to sustain life, as a source of food and for income generation, main source of freshwater supply to the communities, hydro-electric power and many more. Unfortunately, many rivers in Kelantan State in Malaysia are badly polluted, bringing severe negative impacts to habitat and human society. The aims of this paper are to identify the river water pollutants’ sources, to identify the level of awareness among communities regarding river pollution problems and to explore the community’s role and engagement in river water quality conservation. This study uses a mixed method combining quantitative and qualitative methods. For data collection, this study used questionnaires to study selected communities in Pasir Mas, Kelantan and also qualitative interview sessions with relevant stakeholders. From the field survey, it was found that household wastewater disposal, solid waste dumping and river bank erosion were the main sources of pollution in the Kelantan River. Results show that about half the respondents do not know that river water pollution affects the costing in water treatment and gave rise to problems in the water supply. This study recommends public education and awareness campaigns to enhance community awareness, and to involve communities in monitoring and reporting all the activities that occur nearby the river in order to control polluting activities. The model of community-based management of water resources is proposed as a viable model to conserve river water quality towards the sustainability of water resources in the future.